Management in maternal autoantibody-mediated clinical foetal myocardial disease - Murlewska, Julia; Preis, Krzysztof; Słodki, Maciej; Strzelecka, Iwona; Smolewska, Elżbieta; Respondek-Liberska, Maria (Prenatal Cardiology, 2019)
Our group presents our reflections, based on the current literature, concerning the obstetric and rheumatologic management of the foetus identified with clinical myocardial disease mediated by maternal autoantibodies (MAb). The European League Against Rheumatism (EULAR) have recommended the use of hydroxychloroquine (HCQ) during asymptomatic lupus pregnancies since 2007. Foetal echocardiography is indicated if there is suspected foetal dysrhythmia or myocarditis, especially in the involvement of positive maternal anti-Ro/SSA or anti-La/SSB antibodies weekly from 16 weeks of gestation upwards. The obstetric management should be guided by the degree of cardiac failure on foetal echocardiography. Foetal therapy with steroids, intravenous immunoglobulin (IVIG), and plasmapheresis should be reasonably introduced in the lowest effective doses for the shortest duration of time. The aim of the management should be to reverse incomplete heart block and other MAb-mediated foetal myocardial disease, presumably induced due to ongoing inflammation. In irreversible cases the treatment should be stopped, due to its possible maternal side effects. Delivery of the affected newborn should be performed in a tertiary centre, and pacemaker implantation might be an option for neonates.